The long non-coding RNA NNT-AS1 promotes clear cell renal cell carcinoma progression via regulation of the miR-137/ Y-box binding protein 1 axis. Issue 1 (1st January 2021) - Zhou, Yadi; Zhang, Zhenghao; Wo, Mingyi; Xu, Wenfang
ABSTRACT: Long noncoding RNAs (lncRNAs) have been implicated in the progression of malignant tumors, including in clear cell renal cell carcinoma (ccRCC). However, the function and the specific mechanism of lncRNA nicotinamide nucleotide transhydrogenase antisense RNA 1 (NNT-AS1) in ccRCC remains unknown. Thus, this study explored the role of NNT-AS1 in ccRCC. We evaluated NNT-AS1 expression in ccRCC specimens. Next, CCK-8 and Transwell assays were used to evaluate cell proliferation and metastatic abilities. The interaction between miR-137 and NNT-AS1 or Y-box binding protein 1 (YBX-1) was confirmed using a dual luciferase reporter assay. The results showed that NNT-AS1 was significantly upregulated in ccRCC specimens compared with normal tissues. Inhibition of NNT-AS1 restrained ccRCC proliferation and metastasis. Mechanistically, NNT-AS1 acted as a competitive endogenous RNA to sponge miR-137, which depressed ccRCC cells proliferation and metastasis. Moreover, with the use of bioinformatics analysis, the famous oncogene YBX-1 was selected as the potential target of miR-137. Luciferase assay also confirmed the interaction between miR-137 and YBX-1. Further functional studies demonstrated that the inhibition effect of NNT-AS1 knockdown on ccRCC carcinogenesis could be partially reversed by overexpression of YBX-1, suggesting that NNT-AS1 promotes ccRCC progression through the miR-137/YBX-1 pathway. In summary, these findings indicate that NNT-AS1 promotes ccRCC progression via the miR-137/YBX-1 pathway, which may provide a promising therapeutic target for renal cell carcinoma.